Global Food Security: Diplomacy and Conflict Amidst the Climate Crisis and Changing Production Patterns - Loso Judijanto (Synergisia, 2025)
Global food security is increasingly threatened by climate change, geopolitical conflicts, and shifting agricultural production patterns. Extreme weather events such as droughts, floods, and irregular rainfall have significant impacts on agricultural productivity, exacerbating food shortages, especially in vulnerable areas. In addition, armed conflicts in countries such as Somalia, South Sudan, Yemen, and Afghanistan further exacerbate food security by disrupting agricultural infrastructure and food distribution systems. This study uses a qualitative approach with descriptive-analytical methods, utilizing a literature review of academic journals, reports from international organizations, and policy documents. Data analysis was conducted using content analysis and comparative analysis to identify key patterns and strategies in food security across regions. The results show that the climate crisis and armed conflict are key drivers of food insecurity, with direct consequences for food availability, accessibility, and stability. In addition, major global actors, including China, the European Union, and Russia, are using food diplomacy as a strategic tool in international relations, impacting global trade and political stability. Furthermore, technological advances in precision agriculture, artificial intelligence, hydroponics, and smart irrigation have emerged as potential solutions to improve food security, albeit with challenges related to accessibility and implementation costs. Studies show that sustainable food policies, international cooperation, and technology adoption must be prioritized to effectively address food security challenges. Strengthening global trade networks, enhancing climate adaptation strategies, and promoting diplomatic efforts to resolve conflicts are important steps towards a more resilient global food system.